2008
DOI: 10.1074/jbc.m705781200
|View full text |Cite
|
Sign up to set email alerts
|

Mutation of Gly721 Alters DNA Topoisomerase I Active Site Architecture and Sensitivity to Camptothecin

Abstract: DNA topoisomerase I (Top1p) catalyzes the relaxation of supercoiled DNA via a concerted mechanism of DNA strand cleavage and religation. Top1p is the cellular target of the anticancer drug camptothecin (CPT), which reversibly stabilizes a covalent enzyme-DNA intermediate. Top1p clamps around duplex DNA, wherein the core and C-terminal domains are connected by extended ␣-helices (linker domain), which position the active site Tyr of the C-terminal domain within the catalytic pocket. The physical connection of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…These results demonstrate that hTdp1 functions in yeast in the presence of hTop1, and that the toxic phenotypes of the two yTdp1 mutants H432R and H432N mutants are also manifested by the equivalent hTdp1 mutants. Comparing yeast Top1-Tdp1 to human Top1-Tdp1, it can be seen that the mutant phenotypes are not strictly equivalent, particularly in the case of the His to Asn substitution, but this may be related to species specific differences in hTop1 function in yeast 30; 31; 32; 33 . It has been shown that hTop1 expression in yeast provides the appropriate DNA topoisomerase I activity and conversely, expression of yTop1 in mammalian cells provides the appropriate activity and CPT sensitivity 30; 34 .…”
Section: Resultsmentioning
confidence: 99%
“…These results demonstrate that hTdp1 functions in yeast in the presence of hTop1, and that the toxic phenotypes of the two yTdp1 mutants H432R and H432N mutants are also manifested by the equivalent hTdp1 mutants. Comparing yeast Top1-Tdp1 to human Top1-Tdp1, it can be seen that the mutant phenotypes are not strictly equivalent, particularly in the case of the His to Asn substitution, but this may be related to species specific differences in hTop1 function in yeast 30; 31; 32; 33 . It has been shown that hTop1 expression in yeast provides the appropriate DNA topoisomerase I activity and conversely, expression of yTop1 in mammalian cells provides the appropriate activity and CPT sensitivity 30; 34 .…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, a Top1D677G/V703I mutant has reduced linker flexibility and is hypersensitive to CPT (29). In addition, replacing Gly 721 with residues estimated to have a higher propensity for ␣ helix formation (Ala or Asp) induced alterations in yeast Top1 active site architecture that increased enzyme sensitivity to CPT (28). In co-crystal structures, the extension of a short ␣ helix within the active site of Topo70 to include Gly 717 coincides with drug binding and a restriction of linker orientation (7).…”
Section: Discussionmentioning
confidence: 99%
“…Lysates were normalized for total protein, and Top1 protein levels were verified by immunoblotting and chemiluminescence using the M2-FLAG antibody (Sigma). Wild-type and chimeric Top1 were partially purified by phosphocellulose chromatography or purified to homogeneity by phosphocellulose and FLAG affinity chromatography, as described (12,28). Top1 protein fractions were adjusted to a final concentration of 30% glycerol and stored at Ϫ20°C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Linker flexibility also impacts mutation-induced alterations in enzymecatalyzed DNA cleavage/religation (24). Indeed, our recent studies suggest that a conserved Gly within the catalytic pocket of Top1 provides a flexible hinge to facilitate linker mobility (26).…”
mentioning
confidence: 99%